The Impact of Financial Literacy and E-Money Use on Transaction Decisions at Warkop Iwan - Putri, Dinda Ameliani; Lubis, Kartika Sari (Universitas Batanghari, 2024)
The rapid development of technology is marked by advances in technology and has entered the digital era. This is characterized by the use of cashless-based payments. One payment method that is currently developing is to use e-money. E-money as a means of payment is quite helpful in the payment process easily, quickly and reliably. This is one of the factors that becomes a person's decision to make a transaction. In addition, financial literacy is important as knowledge in the use of finance to decide someone to transact. The purpose of this study is to analyze the effect of financial literacy and the use of e-money on transaction decisions. This research method is using quantitative research with the object of research of Warkop Iwan customers taken by 99 respondents. The analysis was performed using SmartPLS. The results showed that financial literacy and the use of e-money on transaction decisions at Warkop Iwan.